A Evaluation of Averrhoa bilimbi L. Acidified Turmeric as a Feed Additive for Broiler under High Density: Modulation of gut microbiota and health broiler under stocking density - Anugrah Robby Pratama Robby; Sri Sumarsih (Mediagro: Jurnal Ilmu-ilmu Pertanian, 2026)
This study investigated the effects of acidified turmeric powder with Averrhoa bilimbi L. fruit filtrate on gut health in broiler chickens raised under high stocking density. A total of 285 Lohmann strain broiler chicks (14 days old, 370 ± 9.02 g) were randomly assigned to four treatment groups: CONT1 (normal stocking density, 9 birds/m², basal diet), CONT2 (high stocking density, 16 birds/m², basal diet), BDTP (16 birds/m², basal diet + 1% turmeric powder), and BDAT (16 birds/m², basal diet + 1% acidified turmeric powder). At 37 days of age, ileal and cecal digesta samples were collected for bacterial analyze, and intestinal pH was measured. In the ileum, BDAT showed reduced coliform counts (p < 0.01) compared to control, while lactic acid bacteria (LAB) was decreased in all treatment groups. Enterobacteriaceae counts did not differ significantly among treatments. Cecal bacterial populations were not significantly affected by the treatments. Intestinal pH values in the duodenum, jejunum, ileum, and cecum did not differ significantly among treatments. Acidified turmeric powder effectively recuce harmfull coliform while preserving the overall microbial balance reared high density. This findings highlight its potential as a alternative feed to promote gut health in intensive broiler production system.